Digital determinants of sexual and reproductive health—workforce perspectives on digital and data literacies. - Albury, Kath; Mannix, Samantha (Health Promotion International, 2025)
This article explores the impact of digital transformation on sexual and reproductive health promotion from an interdisciplinary perspective, focusing on the implications of rapidly evolving policy landscapes for the Australian health promotion workforce. We draw on 29 key informant interviews and workshops with 18 current sexual and reproductive health professionals (aged 18–29). Both groups were invited to reflect on how digital and data literacies are currently understood and applied within the Australian sexual and reproductive health promotion sector. Interviewees shared concerns related to digital and data literacy, equity, and the challenges of integrating digital technologies into health practice. Findings highlight the need for strategic approaches that shift focus away from individual literacies towards broader organisational capabilities. These capabilities include: an understanding of digital policy and platform governance (e.g. in relation to social media content moderation); an understanding of how health consumers and service users currently utilise digital systems to support sexual health and wellbeing; and an understanding of the ways digital equity and data justice can be undermined or advanced in organisational settings. We conclude with recommendations for enhancing workforce digital and data capabilities and integrating DDoH into health promotion policy and practice to improve health equity. Significantly, we conclude that dedicated resources and training are needed to address the complexities of DDoH in the sexual and reproductive health context.